2022
DOI: 10.1101/2022.09.26.22280249
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiology and risk factors for diarrhoeagenic Escherichia coli carriage among children in northern Ibadan, Nigeria

Abstract: Diarrhea is a leading cause of childhood morbidity in Africa. Outside of multi-country sentinels, of which there are none in Nigeria, few studies focus on bacterial etiology. We performed a case-control study among children under five years of age. Stool specimens were collected from 120 children with, and 357 without, diarrhea attending primary health clinics on the northern outskirts of Ibadan between November 2015 and August 2019. Up to ten E. coli isolates were obtained per specimen and at least three we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 62 publications
2
15
0
Order By: Relevance
“…Up to ten isolates were obtained per stool specimen and all isolates were subjected to PCR screening. Up to three isolates showing different biochemical and/or Whole genome Sequencing: E. coli genomic DNA were extracted using the Wizard Genomic Extraction kit (Promega) according to the manufacturer's instructions and they were shipped and bulk sequenced in Sanger using the illumina platform as described previously (6). Raw data were assembled by SPAdes assembler and assembly quality was determined using Quality Assessment Tool for Genome Assemblies (QUAST), and CheckM.…”
Section: Strainsmentioning
confidence: 99%
See 4 more Smart Citations
“…Up to ten isolates were obtained per stool specimen and all isolates were subjected to PCR screening. Up to three isolates showing different biochemical and/or Whole genome Sequencing: E. coli genomic DNA were extracted using the Wizard Genomic Extraction kit (Promega) according to the manufacturer's instructions and they were shipped and bulk sequenced in Sanger using the illumina platform as described previously (6). Raw data were assembled by SPAdes assembler and assembly quality was determined using Quality Assessment Tool for Genome Assemblies (QUAST), and CheckM.…”
Section: Strainsmentioning
confidence: 99%
“…It is common among EAEC strains from some locations, for example the Chile and India strain sets on which that the "EAEC probe" Baudry et al (1990) was validated (50). However subsequent data has shown that CVD432-negative EAEC strains predominate in some geographies, including Nigeria (6,51). The insensitivity of CVD432-based PCR protocols and could be resolved, at least in part by using additional targets as Czeuczulin et al and Boisen et al (52,53) have recommended.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
See 3 more Smart Citations